Słowniczek tykociński Zygmunta Glogera – źródła i dokumentacja - Nowowiejski, Bogusław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The article focuses on lexicographic means and methods used in the 19th century dialectal lexicography. Zygmunt Gloger in Tykocin Dictionary refers not only to dialect but also to other sources, which makes his work unique. It contains numerous references, especially to literary and historical texts, but also specialised papers. They serve either to prove the presence of a particular word/phrase in the Polish language in the past or in the times of Gloger, or to document the use of selected units in various syntactic and semantic contexts. Scientific references enable to define and to deepen etymology of selected words, or to provide an alternative variation. Referring to various sources in order to show historically or/and geographically determined phonetic, morphological and semantic-lexical forms that differ from forms in Tykocin Dictionary is rare.